“Como é que vou dizer...” : a coconstrução de sentidos nas narrativas orais de uma pessoa com atrofia cortical posterior - Custodio, Katiuscia de Almeida (Universidade do Vale do Rio dos Sinos, 2019)
Posterior Cortical Atrophy (PCA) is a neurodegeneration that affects the language and, consequently, the interactions of those who are affected by this pathology in their various daily relations. In view of this situation, this thesis seeks to discuss the intrinsic relationship between interaction, language and cognition, aiming to analyze a person affected by posterior cortical atrophy’s participation in daily oral interactions, verifying the way in which the speech is realized from a textual-interactive perspective. To this end, this research follows a qualitative design, based on three research fields: Conversation Analysis (MARCUSCHI, 1986), Oral Narrative studies—more specifically, the narrative dimension approach proposed by Ochs and Capps (2001)—and Textual Linguistics, particularly the notion of referral (REICHLER-BÉGUELIN, 1988; MONDADA; DUBOIS, 2003; MARCUSCHI; KOCH, 2006). This work’s corpus consists of audio and video recordings of interactions between a researcher and a participant diagnosed with PCA, without a pre-established script, covering the period between April, 2016 and August, 2017. The analysis of this corpus allowed us to verify that the participant diagnosed with PCA performs different linguistic and discursive strategies during face-to-face interactions to interact in everyday conversational situations. Among these strategies we highlight the co-constructed narratives that emerge and are integrated into the discursive topic of interaction. It is possible to observe in our data that, in the PCA context, narratives are interactively co-constructed, not only characterizing a way of reporting facts, but also a process of constructing referents with the interlocutor. Our analyses demonstrate that the collaborative nature of language overlays the difficulties imposed by the participant’s pathology, making use of several sociocognitive strategies in order to remain active in the course of interaction. Furthermore, the narratives performed by Joana, participant of this study diagnosed with PCA, coupled with the discourse at play, reveal a fundamental characteristic of co-construction, combining the textual-interactive materiality that occurs in narrative performance with the different forms she uses while shaping the act of telling stories with an interlocutor. The analyses show that in telling a story, Joana is more than simply narrating a fact. Through this discursive activity, the participant co-constructs referents with the interlocutor, evidencing the sociocognitive work of language, in a collaborative attitude, as proposed by Clark (1992; 1996) as being a proper attribute of language, the joint action intrinsic to everyday interactional practices. Moreover, these narratives, as they present a more flexible structure and allow co-narration, establish themselves as an interactional area through which Joan re-signifies her experiences, reactivates her memories and negotiates meanings with the interlocutor demonstrating the sociocognitive activity that helps her to circumvent language deficits (caused by the disease) that arise during the interactions, relying on the interactions of the interacting agent.
Keywords: Atrofia Cortical Posterior; Referenciação; Narrativas Orais; Posterior Cortical Atrophy; Referral; Oral Narratives; ACCNPQ::Lingüística, Letras e Artes::Lingüística